The Escolinha de Artes in Recife as an inclusive space for people with deficiency (Revista de Ensino em Artes, Moda e Design, 2020)
The Escolinha de Arte do Recife since its origin, in 1953, has been developing art/ educational activities for all types of public. Noting the historical relevance of the institution for Art / education in Pernambuco, bibliographical, historical and docu- mentary records were investigated, as well as the art / educational practices develo- ped there. Based on EAR’s trajectory, we comment on the institution’s inclusive vision and how it has contributed, and still contributes, to the construction of practices in an inclusive perspective for people with disabilities. So according to bibliographic records, documents and the realization and analysis of an art / educational activity developed today, it was observed that Escolinha was, and is, a space where sensory aesthetic experiences are worked from the perspective of inclusion.
Keywords: art; education; inclusion